Perempuan dan Kepemimpinan dalam Pendidikan Islam - Isyatul Mardiyati (PSGA LP2M IAIN Pontianak, 2014)
The discourse of woman leadership in Islamic Education, in terms of religious concept, is still contemporarily hegemonized in a leadership structure at religious-based university. Moreover, at this point, every analysis has a significant argument which ends to gender deconstruction, whether it is possible for woman to perform leadership in an education institution. Besides, it also conveys the legalization of important person in the institution, rector at Islamic University, for instance, as well as Minister of Religion. Therefore, the article densely discusses woman and leadership in Islamic education.